From inequitable to sustainable e-waste processing for reduction of impact on human health and the environment - Ádám, Balázs; Göen, Thomas; Scheepers, Paul T.J.; Adliene, Diana; Batinic, Bojan; Budnik, Lygia T.; Duca, Radu Corneliu; Ghosh, Manosij; Giurgiu, Doina I.; Godderis, Lode; Goksel, Ozlem; Hansen, Karoline K.; et al. (Environmental Research, 2021)
Recycling of electric and electronic waste products (e-waste) which amounted to more than 50 million metric tonnes per year worldwide is a massive and global operation. Unfortunately, an estimated 70–80% of this waste has not been properly managed because the waste went from developed to low-income countries to be dumped into landfills or informally recycled. Such recycling has been carried out either directly on landfill sites or in small, often family-run recycling shops without much regulations or oversights. The process traditionally involved manual dismantling, cleaning with hazardous solvents, burning and melting on open fires, etc., which would generate a variety of toxic substances and exposure/hazards to applicators, family members, proximate residents and the environment. The situation clearly calls for global responsibility to reduce the impact on human health and the environment, especially in developing countries where poor residents have been shouldering the hazardous burden. On the other hand, formal e-waste recycling has been mainly conducted in small scales in industrialized countries. Whether the latter process would impose less risk to populations and environment has not been determined yet. Therefore, the main objectives of this review are: 1. to address current trends and emerging threats of not only informal but also formal e-waste management practices, and 2. to propose adequate measures and interventions. A major recommendation is to conduct independent surveillance of compliance with e-waste trading and processing according to the Basel Ban Amendment. The recycling industry needs to be carefully evaluated by joint effort from international agencies, producing industries and other stakeholders to develop better processes. Subsequent transition to more sustainable and equitable e-waste management solutions should result in more effective use of natural resources, and in prevention of adverse effects on health and the environment.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Basel ban amendment; e-waste; Electronic waste recycling; Environmental pollution; Health hazards